Consumption of Folic Acid, B12 and Menstruation Pattern with Anemia Phenomenon in Young Women in Surabaya - Irine Christiany; Kiaonarni Ongko Waluyo (Health Notions, 2019)
Consumption of folic acid intake, B12 and the pattern of menstruation are factors causing the occurrence of anemia, vitamin B12 and folic deficiency often occurs in young women. Deficiency of one or several nutrients such as iron, vitamin B12, folic acid, and vitamin C, which is necessary for the formation of nutrients can cause nutritional anemia. The purpose of study was to know the intake of folic acid intake, Vitamin B12 and menstruation pattern with the incidence of Anemia in young women in Surabaya Junior High School. Research method was cross sectional approach. The study population of all female students who have menstruated in Surabaya Junior High School was taken by simple random sampling. The research instrument was questionnaire by 24-hour Food Recall and FFQ complement data that could not be obtained through 24-hour memory, menstrual pattern questionnaires and hemoglobin results by measuring hemoglobin (HB) by cyanmethemoglobin method. Data analysis was using logistic regression test. The result was 19.007 (p = 0.000; OR = 31.000-; 95 percent CI = 4.002- 240.150), this means there was a significant association between vitamin B12 intake and the incidence of anemia (p < 0.05), and the menstruation pattern was 10.340 (p = 0.001; OR = 4.846-; 95 percent CI = 1.897- 12.379), this means there was a significant relationship between the pattern of menstruation and the incidence of anemia (p < 0.05). Vitamin B12 intake and menstruation pattern significantly influenced the incidence of anemia (P =